Validation of the Protect Questionnaire: A tool to detect mental health problems in asylum seekers by non-health professionals - Mewes, Ricarda; Friele, Boris; Bloemen, Evert (Torture Journal, 2018)
Introduction: Prevalence rates of trauma-related mental disorders such as posttraumatic stress disorder (PTSD) or major depression (MD) are high in asylum seekers. The PROTECT Questionnaire (PQ) was designed to detect indications of those disorders in asylum seekers. Empirical data are needed to evaluate the PQ psychometrically. The objective of this study is to investigate the reliability, validity, sensitivity, and specificity of the PQ. Method: The PQ and validated questionnaires for PTSD (Posttraumatic Diagnostic Scale, PDS) and depression (Patient Health Questionnaire-9, PHQ- 9) were filled in by a sample of recently arrived asylum seekers in Germany (n=141). A sub-sample of 91 asylum seekers took part in a structured clinical interview to diagnose PTSD or MD (SCID-I). Results: The PQ showed a one-factor structure and good reliability (Cronbach’s ⍺= .82). It correlated highly with the PDS and the PHQ-9 (rs=.53-.77; ps≤.001). Diagnostic accuracy with regard to PTSD (AUC=.74; SE=.06; p<.001; 95%-CI=.63-.84) and MD (AUC=.72; SE=.06; p<.001; 95%-CI=.61- .83) was adequate, suggesting an optimal cut-off of 8 or 9. By categorizing participants into a low- and high-risk category, the PQ differentiated well between asylum seekers who fulfilled a PTSD or MD diagnosis and those who did not. Discussion: The results support the use of the PQ as a reliable and valid instrument for the purpose of detecting signs and symptoms of the two most common mental disorders in asylum seekers. Persons found to be at risk of mental disorders should be referred to a clinical diagnostic procedure.